2007
DOI: 10.1021/jp065291y
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Structure of the Urea−Water System Studied by Dielectric Spectroscopy

Abstract: Dielectric spectroscopy measurements for aqueous urea solutions were performed at 298 K through a concentration range from 0.5 to 9.0 M with frequencies between 200 MHz and 40 GHz. Observed dielectric spectra were well represented by the superposition of two Debye type relaxation processes attributable to the bulk-water clusters and the urea-water coclusters. Our quantitative analysis of the spectra shows that the number of hydration water molecules is approximately two per urea molecule for the lower concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
97
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 25 publications
16
97
1
Order By: Relevance
“…In contrast to prior studies of aqueous salt solutions 41,44,47,48 , the time constants of the relaxations we observe are effectively independent of salt concentration over the entire concentration range we have explored (Fig. 3, top).…”
Section: Introductioncontrasting
confidence: 99%
“…In contrast to prior studies of aqueous salt solutions 41,44,47,48 , the time constants of the relaxations we observe are effectively independent of salt concentration over the entire concentration range we have explored (Fig. 3, top).…”
Section: Introductioncontrasting
confidence: 99%
“…2(a), which shows the high frequency dielectric spectra of BSA solutions at various urea concentrations. This dielectric loss peak is attributed to water and urea molecules based on the observation of similar behavior in urea-water solutions without proteins [12] as shown in Fig. 2(b).…”
Section: Resultsmentioning
confidence: 69%
“…Our previous study for urea-water systems without protein showed that the complex permittivity of a urea-water system can be described by two Debye processes or one Havriliak-Negami (HN) process, but it cannot be described by one CC process [12]. After more detailed data analysis, we concluded that the description by two Debye relaxation processes is more suitable than that by one HN process.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations